PENANGANAN PELANGGARAN KAMPANYE PEMILIHAN UMUM ANGGOTA DPR, DPD DAN DPRD DI WILAYAH KABUPATEN/KOTA - Febry Chrisdanty; Diah Wahyulina (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2014)
The goal of an election is to choose the best leader with great integrity and responsibility. In achieving the goal, the election must be supported by all components involved in it; the administrators, participants, and integrated process. One of the process of the election is campaign. This process is used as the best way to attract people’s interest. Therefore, people will vote a particular candidate in the election day. The candidates of board members will compete to get the highest voter.The one who get the highest vote will be the board member. The rules of the campaign are clearly stated in the regulation. However, there are many violations happened. The votes are meaningless because the process is full of violations, not a fair and democratic process as people desire.